2015
DOI: 10.1007/s10803-015-2518-2
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Subthreshold Autistic Traits, Ambiguous Figure Perception and Divergent Thinking

Abstract: This research investigates the paradox of creativity in autism. That is, whether people with subclinical autistic traits have cognitive styles conducive to creativity or whether they are disadvantaged by the implied cognitive and behavioural rigidity of the autism phenotype. The relationship between divergent thinking (a cognitive component of creativity), perception of ambiguous figures, and self-reported autistic traits was evaluated in 312 individuals in a non-clinical sample. High levels of autistic traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 52 publications
3
31
1
6
Order By: Relevance
“…To the extent that ED and autism are associated (as suggested by Hambrook, Tchanturia, Schmidt, & Treasure [19]), our results are somewhat convergent with Best, Arora, Porter and Doherty [20] who found that degree of subthreshold autistic traits was associated with less flexibility but not less originality.…”
Section: Discussionsupporting
confidence: 88%
“…To the extent that ED and autism are associated (as suggested by Hambrook, Tchanturia, Schmidt, & Treasure [19]), our results are somewhat convergent with Best, Arora, Porter and Doherty [20] who found that degree of subthreshold autistic traits was associated with less flexibility but not less originality.…”
Section: Discussionsupporting
confidence: 88%
“…This resulted in three participant groups: low AQ (n = 15), high AQ (n = 15) and ASD (n = 13). Participants without an ASD diagnosis were grouped into low and high AQ groups due to findings of subtler versions of the behavioural and neural characteristics associated with ASD in individuals without a diagnosis but relatively high levels of autistic traits (Best et al 2015 ; Di Martino et al 2009 ; Lindell et al 2009 ; Ridley et al 2011 ; van Boxtel and Lu 2013 ). AQ scores were used to group these individuals initially and further psychological assessments were later used to quantify the level of autistic traits displayed in more detail (see Psychological Assessments ).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the spectral nature of ASD, individuals without a diagnosis also display varying degrees of autistic traits. Individuals with relatively high but not clinically significant levels of autistic traits have been shown to display subtler versions of the behavioural and neurological characteristics associated with ASD (Best et al 2015 ; Di Martino et al 2009 ; Lindell et al 2009 ; Ridley et al 2011 ; van Boxtel and Lu 2013 ) including mentalizing deficits (Baron-Cohen et al 2001 ; Chung et al 2014 ; Happé 1994 ; Kana et al 2014 ; Moran et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%